Portfolio Deternination and Markowitz Essicient Fronter in Five Indonesian Industrial Sector - Rachmat, Doddy; Nugroho, Anggoro Budi (Journal of Business and Management, 2013)
The goal of this thesis is to construct an optimal and efficient portfolio of 5 Indonesia indsutrial sector stocks. The time horizon of this thesis is from February 2011 until November 2012. There are 2 portfolios that have been created. Those 2 are Maximum Return portfolio, and Minimum Standart Deviation portfolio. The creation of those 2 portfolios was helped by the MS Excel Solver add-ins to determine the weights of each stock in a portfolio. Then those 2 portfolios compared to each other and the market with some performance measurements like Sharpe ratio, Treynor measure, and Jensen’s Alpha. The outputs of this research are the portfolio which generates the highest return also turns out to have the best perfomance among other portfolios based on Sharpe Ratio and Jensen Alpha. This portfolio has a Sharpe Ratio of 19,59% with Jensen Aplha of 0,37%. This research has its scope and limited based on stocks that has been chosen by the writer which consistently included in the index from February 2012 until November 2012. All the stocks that the writer chose is based on the fundamental factor of each stock such as Price Earning Ratio (PER), Earning per Share (EPS), Return on Asset (ROA), and Return on Equity (ROE) which is often used by the investors to analize the company’s stocks for long term investment. The outcome of this thesis is an investment to the Maximum return portfolio which has the best performance among the other portfolios and the market from February 2011 until November 2012. This research creates an optimal and efficient portfolio of Five Indonesian indsutrial sector for investors. Keywords: Portfolio Construction, Performance Analysis, Sharpe Ratio, Treynor’s Measure, Jensen Alpha.Category: Finance; Performance Management.